Comment: Old Wine in New Bags—Suri and Gross's Connectionist Theory of Emotion is Another Type of Network Theory. (April 2022) - Moors, Agnes
Suri and Gross's 2022 connectionist emotion theory can be considered as one version of a family of theories known as network theories of emotion. It presents similarities and differences with older versions of network theories. Like previous network theories and several other traditional emotion theories, however, the connectionist theory remains a reactive theory. The class of reactive theories can be meaningfully contrasted with a class of instrumental theories of which the goal-directed theory is a representative example. Although the latter theory does not deny the existence of emotion networks in memory, it does not grant them many causal powers, thereby seriously restricting their explanatory territory. Future research efforts may help disambiguate between both classes of theories.